Mobile Network Leader: A New Role of the Leader in Corporate Management - Haber Lesław H. (Management, 2015)
The purpose of this paper was to present the management system evolution, from functional to process to network management. The network management system requires new organizational solutions associated with the fulfilment of external functions in management, directed at the acquisition of stakeholders from the environment who are treated as relational capital. That also requires new skills and competences in searching for relational capital. Possession of that type of capital indicates the importance of a company on a competitive market. The author pointed out the significance of the mobile network leaders’ personal traits, from the viewpoint of their causative power in searching for relational capital. It was pointed out that not every mobile network leader may possess specific personal capabilities to attain relevant objectives.